Keynes and Polanyi: the 1920s and the 1990s - Polanyi Levitt, Kari (Review of International Political Economy, 2006)
Keywords: KEYNES, John Maynard, 1883-1946; international political economy

From the Great Transformation to the Great Financialization: On Karl Polanyi and Other Essays - Polanyi Levitt, Kari (Zed Books, 2013)
Four years into the unfolding of the most serious crisis since the 1930s, Karl Polanyi's prediction of the fateful consequences of unleashing the destructive power of unregulated market capitalism on peoples, nations, and the natural environment have assumed new urgency and relevance. Polanyi's insistence that 'the self-regulating market' must be made subordinate to democracy otherwise society itself may be put at risk is as true today as it was when Polanyi wrote. Written from the unique perspective of his daughter, From the Great Transformation to the Great Financialization is an essential contribution to our understanding of the evolution and contemporary significance of Karl Polanyi's work, and should be read against the background of the accelerating accumulation of global finance that created a series of financial crises in Latin America, Russia, Asia, and, eventually, the heartlands of capitalism itself.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Latin America; business & economics; economic conditions; economic development; economic history; global financial crisis; political economy; political science

Los conceptos más importantes en el trabajo de Karl Polanyi y su relevancia contemporánea - Polanyi Levitt, Kari (Economía y Desarrollo, 2014)
El artículo se centra en la vida y obra del historiador Karl Polanyi, quien escribió el libro "La Gran Transformación", en 2014 y también discute la investigación realizada sobre la vida económica de las sociedades primitivas por Polanyi.
Keywords: Great Transformation, The (Book); primitive societies

Karl Polanyi as a Development Economist - Polanyi Levitt, Kari (Pioneers of Development Economics: Great Economists on Development, 2005)
The history of modern economic thought has been pre-occupied with the question of economic transformation or development. This survey of important contributions to the economics of development includes many economists not normally considered as pioneers in this field. The contributors point to the role of imperialist considerations in the early development of economic thought and the development discourse, and the impact of pressures for social and political reform. The economists and thinkers discussed include William Petty, David Ricardo, Friedrich List, Alexander Hamilton, Karl Marx, Vladimir Ilyich Lenin, Alfred Marshall, Michal Kalecki, John Maynard Keynes, Nicholas Kaldor, Karl Polanyi, Raul Prebisch, Arthur Lewis, Alexander Gerschenkeron and Hans Singe
Keywords: development economics; economic history

Karl Polanyi in Vienna: The Contemporary Significance of The Great Transformation - Polanyi Levitt, Kari; McRobbie, Kenneth (Black Rose Books, 2006)
Karl Polanyi’s belief that the greatest threat to freedom was a poorly administered economy led him to an economics that was more existential and human-centered. Part I of this book develops Polanyi’s thinking for its significance today through a selection of papers on re-reading his major work entitled The Great Transformation. Part II looks at the life and work of Ilona Duczynska (Polanyi’s wife), political activist, writer and translator and important influence over Karl and his work. Kenneth McRobbie, a poet and historian who teaches at the University of British Columbia, is the editor of Humanity, Society and Commitment. Kari Polanyi Levitt, emeritus professor at McGill University, is the editor of The Life and Work of Karl Polanyi.
Keywords: autobiography; biography; business & economics

Karl Polanyi - The Life and Works of an Epochal Thinker - Thurnher, Armin; Aulenbacher, Brigitte; Novy, Andreas; Marterbauer, Markus; Polanyi Levitt, Kari (2020)
On 8 May 2018, the International Karl Polanyi Society was founded in Vienna. This marked the beginning of a new phase of engagement with a thinker who had already come to be regarded as a centennial figure in the Anglo-Saxon world. This book serves as an introduction to The Great Transformation, Polanyi’s magnum opus and one of the most important works of the 20th century. It helps us to understand the background to Karl Polanyi’s intellectual career, sketches the lives of his family members, describes the milieus of Budapest, Vienna, London and New York, which were such informative influences in his life, and sheds light on his relationship with contemporaries such as Keynes, Mises and Hayek. Renowned Polanyi researchers, including, most notably his daughter Kari Polanyi Levitt, elucidate Polanyian concepts such as ‘fictitious commodities’ and apply his analysis to an era when everything seems to be subjected to the mechanics of the market.
Keywords: Great Transformation, The (Book); fictitious commodities